1990
DOI: 10.2307/1940251
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Concentrations in Extrafloral Nectar of Impatiens Sultani Increase after Simulated Herbivory

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology.Abstract. In many plants, extrafloral nectars attract ants that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 25 publications
4
62
0
4
Order By: Relevance
“…Similar effects were found in two field experiments that were conducted in different years. These results are in line with earlier reports indicating that EFN flow might be induced by herbivory (10,(13)(14)(15), and that this reaction does not require herbivore-specific elicitors (16,17). Exogenous application of the plant stress hormone JA led to a comparable increase in EFN flow ( Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similar effects were found in two field experiments that were conducted in different years. These results are in line with earlier reports indicating that EFN flow might be induced by herbivory (10,(13)(14)(15), and that this reaction does not require herbivore-specific elicitors (16,17). Exogenous application of the plant stress hormone JA led to a comparable increase in EFN flow ( Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Given a choice, ants forage preferentially on plants with extrafloral nectaries (5-7), and several ant and wasp species directly defend the nectary-bearing plant parts against other insects (8). Both insect groups reduce numbers of herbivorous insects on plants possessing extrafloral nectaries and thus lessen damage by herbivores (5,6,(8)(9)(10)(11)(12).Several studies have already indicated that EFN secretion or amino acid concentrations in EFN may increase in response to herbivory (10,(13)(14)(15) and that this reaction does not require herbivore-specific elicitors (16,17). However, most of these studies have suffered from methodological problems (discussed in ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…He diluted the nectar of individual nectaries with water and demonstrated that the diluted nectar collected from sphingid-damaged leaves was richer in solutes compared with nectar collected from undamaged leaves. Smith et al (1990) point out that this does not resolve whether C. speciosa actually increased its nectar volume or whether it produced the same volume with an increased solute concentration. Koptur (1989) reported that mechanical damage of Vicia sativa leaves increased the volume of extrafloral nectar production by a factor of 2.5.…”
Section: Induction Of Food Provisionmentioning
confidence: 95%
“…In addition to carbohydrates, extrafloral nectar may contain variable amounts of proteins, amino acids, and lipids (Baker et al, 1978;Smith et al, 1990). The particular amino acid composition can increase the attractiveness of extrafloral nectar as a food source (Lanza, 1988).…”
Section: Plant-provided Nutrition and Its Functionsmentioning
confidence: 99%